2002
DOI: 10.1021/ol027236n
|View full text |Cite
|
Sign up to set email alerts
|

Increased Felkin−Anh Selectivity Using AlMe3in the Addition of Vinyllithiums to α-Chiral Aldehydes:  Do “Ate” Complexes Play Any Role?

Abstract: [reaction: see text] AlMe(3) dramatically increases the diastereoselectivity of addition of vinyllithiums to alpha-chiral aldehydes but decreases that of methyllithium. Our results are explained in terms of an addition of the free vinyllithium on the Me(3)Al-aldehyde complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Similarly, addition of alkenyllithium in the presence of AlMe 3 was effective in avoiding the deiodination (Table 1, entries 1e3, 6, 8, and 9). 18 However, since this reaction was often accompanied by addition of a methyl group (derived from AlMe 3 ) to the aldehyde, the Grignard method is considered more advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, addition of alkenyllithium in the presence of AlMe 3 was effective in avoiding the deiodination (Table 1, entries 1e3, 6, 8, and 9). 18 However, since this reaction was often accompanied by addition of a methyl group (derived from AlMe 3 ) to the aldehyde, the Grignard method is considered more advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…Additives such as MgBr 2 ·(OEt) 2 and Yb(OTf) 3 [26] (OTf = trifluoromethanesulfonate) were employed, but the desired product was not obtained (see Table 1, Entries 2 and 3). The employment of AlMe 3 [27] and ZnMe 2 [28] led to an epimeric mixture of alcohols 3a and 3b in low yields with low stereoselectivity, and alkene 5 was again the major product (see Table 1, Entries 4-6).…”
Section: Resultsmentioning
confidence: 99%
“…brought the level of stereoselectivity to a whopping 100 : 1. 31 Strangely, the use of exactly 1 equiv. of AlMe 3 leads to a sluggish and incomplete reaction.…”
Section: Alkylations To Make 41 Chiral Carbonsmentioning
confidence: 99%
“…We demonstrated that AlMe 3 increased the Felkin-Ahn selectivity of the addition of vinyllithium reagents to many other a-chiral aldehydes. 31 Cerium trichloride will also somewhat increase the stereoselectivity of addition of alkynyllithium reagents to a-chiral aldehydes. 33 At this stage, we could have looked more extensively for other aldehydes that may not require an additive such as AlMe 3 to yield diastereomerically pure allylic alcohols like 46. a-Alkoxyaldehydes and Garner's aldehyde 34 were considered, but the presence of heteroatoms on the chiral auxiliary could be detrimental to the overall sequence since we used such reactants as cuprates and ozone in it.…”
Section: Alkylations To Make 41 Chiral Carbonsmentioning
confidence: 99%